Adaptation of international coronavirus disease 2019 and breast cancer guidelines to local context - Valencia, GA (2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (a novel coronavirus), which was first identified amid an outbreak of respiratory illness cases in Wuhan, China and declared a global health emergency, is currently considered an additional challenge in the management of patients with breast cancer (BC). Cancer patients are more vulnerable to becoming infected with severe acute respiratory syndrome coronavirus 2 and are more likely to suffer additional complications that can increase mortality. Identifying those BC patients who require more urgent therapy than others in the current situation is essential. These recommendations are based on and have been adapted from those similarly published by international scientific societies for BC management. They are divided mainly by clinical stage (early, advanced), subtype [luminal, human epidermal growth factor receptor 2 (HER2), triple-negative], or type of medical treatment and setting (neoadjuvant, adjuvant, metastatic). Recommendations for HER2 and triple-negative subtypes are similar, whereas in luminal subtype there are various options of management. The objective is to adapt guidelines to local context through relevant decision-makers, avoiding duplication of efforts and optimizing use or resources. We hope that these recommendations will help medical oncologists provide the best quality care to BC patients during the COVID-19 pandemic with information tailored to our healthcare system. Aim: To establish and adapt recommendations from those published by international scientific societies for BC management. Methods: The Peruvian Society of Medical Oncology developed a consensus and propose here a manuscript with recommendations for oncological medical treatment of BC during the COVID-19 pandemic. The Peruvian Society of Medical Oncology invited a panel of experts and opinion leaders on BC working in major health care systems around Peru. Panel experts selected three international clinical practice guidelines (National Comprehensive Cancer Network, European Society for Medical Oncology, Spanish Foundation Research Group in Breast Cancer), considering that these are more representative in COVID-19 management. Also, the panel agreed to include at least one European and American clinical practice guideline. Results: Recommendations about BC management during the COVID-19 pandemic were divided mainly by clinical stage (early, advanced), subtype (luminal, HER2, triple-negative), or type of medical treatment and setting (neoadjuvant, adjuvant, metastatic). Recommendations for HER2 and triple-negative subtypes were similar between clinical practice guidelines, whereas in luminal subtype there were various options of management. One hundred twelve recommendations were reviewed, adapted, and voted. A consensus was made in order to provide best decisions of management, avoid duplication of efforts, and optimize medical resources, considering health care system reality. These recommendations are not intended to replace clinical judgment.Conclusion: Most of recommendations are similar, mainly in high-risk subtypes (HER2, triple-negative). Certain societies adapt them to deal with different situations involving the best decision in the management of BC patients.